Unveiling the mechanism of core–shell formation by counting therelative occurrence of microstates - Paz, Sergio Alexis (2014)
A procedure usually applied to construct free energy surfaces for a system at equilibrium is found here useful for obtain information on a non-equilibrium process. The joint probability of observing collective variables from a swarm of irreversible molecular dynamic trajectories is analyzed. This straightforward procedure can supply detailed mechanistic information on the irreversible coalescence of two particles made of 42 Au atoms and 13 Co atoms respectively. A complex mechanistic behavior is unveiled using the analysis proposed. This is performed without the need to compute large databases containing minima and transition rates, as required by master equation methods.